2000
DOI: 10.1097/00004032-200006000-00009
|View full text |Cite
|
Sign up to set email alerts
|

Orally Administered Ethane-1-Hydroxy-1,1-Biphosphonate Reduces the Lethal Effect of Oral Uranium Poisoning

Abstract: Intoxication with uranium compounds is both an occupational risk for the workers engaged in the different processes of the elaboration of nuclear fuel and a risk for the population at large in terms of contaminated water and food. The toxic effects of uranium can be reduced by the administration of a biphosphonate, ethane-1-hydroxy-1,1-biphosphonate (EHBP), subcutaneously or intraperitoneally. The aim of the present work was to examine whether orally administered EHBP reduces the lethal effect of a single oral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(16 citation statements)
references
References 17 publications
2
14
0
Order By: Relevance
“…Bioavailable uranium could link to EHBP in blood conforming chelates that allow uranium to be excreted supressing its effect as a life-threatening compound. Our group has extensive evidence on the preventive effect of EHBP for acute uranium intoxications administered intraperitoneally (Ubios et al, 1994), subcutaneously (Ubios et al, 1998;Martinez et al, 2000) or orally (Martinez et al, 2000). In all cases we demonstrated that EHBP is able to ameliorate the structural and functional damages induced by uranium.…”
Section: Inhibition Of Uranium Toxicitysupporting
confidence: 54%
See 2 more Smart Citations
“…Bioavailable uranium could link to EHBP in blood conforming chelates that allow uranium to be excreted supressing its effect as a life-threatening compound. Our group has extensive evidence on the preventive effect of EHBP for acute uranium intoxications administered intraperitoneally (Ubios et al, 1994), subcutaneously (Ubios et al, 1998;Martinez et al, 2000) or orally (Martinez et al, 2000). In all cases we demonstrated that EHBP is able to ameliorate the structural and functional damages induced by uranium.…”
Section: Inhibition Of Uranium Toxicitysupporting
confidence: 54%
“…The longest survival time was observed for suckling animals (Ubios et al, 1994) when compared to adult animals (Martinez et al, 2000). Again, the efficiency of the treatment depended on the time lapse between exposure to the toxicant and the administration of the bisphosphonate proving that efficency is inversely proportional to the time interval (Ubios et al, 1998).…”
Section: Inhibition Of Uranium Toxicitymentioning
confidence: 98%
See 1 more Smart Citation
“…Many chelating agents such as 3,4,3-LIHOPO [19,[34][35][36], Tiron [37,38], ethane-1-hydroxy-1,1-bisphosphonate (EHBP) [39][40][41]46], deferiprone (L1) 1,2-dimethyl-3-hydroxypyrid-4-one [42], DTPA [43], CBMIDA [44] and 1,2-diamino cyclohexyl-tetramethylenetetraphosphonate (CTTP) [45] have been examined for the removal of uranium (Table 4). Although DPTA is often said that it can remove uranium from the body, its effectiveness remains unclear…”
Section: The Use Of Chelating Agents For Minimizing Uranium Body Incomentioning
confidence: 99%
“…Several uranyl ligands had been synthesized based on different complexing functions (containing ethane-1-hydroxy-1,1-bisphosphonate and methylterphthalimide metal binding units). However, their high toxicity or low decorporation efficacy is not suitable for biological decorporation [7][8][9][10][11]. The use of multidentate ligands containing the catecholate functionality as binding units, such as sulfocatechol tiron (4,5-dihydroxy-3,5-benzenedisulfonate), which were of a low to mild toxicity [12][13][14] and can reduce uranium in the body of animals when promptly injected [15][16][17], and the U(VI)-catechol complex (Log K ML = 15.9), which is favorably stable within the physiological pH range [18], might be effective for the in vivo chelation of U(VI).…”
Section: Introductionmentioning
confidence: 99%